Analysis of Students’ Responses on Genetics Learning Integrated with The Lilian Cultural Values of Moloku Kie Raha Sultanate Society - Roini, Chumidach; Limatahu, Iqbal; Mas'ud, Abdu; Suparman, Suparman; Rasyid, Magfirah (JURNAL BIOEDUKASI, 2025)
Students' understanding of genetic concepts generally varies; some students are able to understand the basic concepts well, but many still have difficulties. This survey was conducted to determine students' responses after completing the Basic Genetics course, which integrated the local wisdom values of the Lilian culture of the Moloku Kie Raha Sultanate. The respondents of this study were third- and fifth-semester students enrolled in the Basic Genetics course, Biology Education Study Program, FKIP, Khairun University. Data collection was carried out using a Likert scale questionnaire to determine student responses to the learning that had been implemented. The results showed positive responses from students regarding learning with practical methods integrated with Lilian cultural values, which can increase student interest and involvement, with 54.9% stating strongly agree, 37.1% agree, 12.9% neutral, while disagree and strongly disagree obtained a score of 0%. These results indicate that the learning that has been implemented has significant implications for students, by increasing their involvement and understanding of genetic concepts.